2016
DOI: 10.1016/j.sjopt.2016.02.007
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of squamous intraepithelial neoplasia in pterygium related to low ultraviolet light exposure

Abstract: The relatively high rate of dysplasia in a low ultraviolet light index area challenges the main cause of this disease in our population, a hypothesis that should be evaluated in future studies. We suggest that all PT samples should be sent for histopathological evaluation even in areas with low ultraviolet light index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…A large study reviewing 3,021 histopathological reports of conjunctival lesions found that the frequency of unsuspected OSSN within pterygium is 0.65% [ 11 ]. In a second study performed in Canada, the reported rate of OSSN is 2.33% [ 20 ]. As both these percentages are based on a search through histopathological reports, we suspect this number to be an underrepresentation of the reality as not all excised pterygiums are sent for histopathological review, and, when they are, there is no consensus on reporting of these lesions.…”
Section: Discussionmentioning
confidence: 99%
“…A large study reviewing 3,021 histopathological reports of conjunctival lesions found that the frequency of unsuspected OSSN within pterygium is 0.65% [ 11 ]. In a second study performed in Canada, the reported rate of OSSN is 2.33% [ 20 ]. As both these percentages are based on a search through histopathological reports, we suspect this number to be an underrepresentation of the reality as not all excised pterygiums are sent for histopathological review, and, when they are, there is no consensus on reporting of these lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, massive amounts of immunoglobulins, such as IgG and IgE, have been found in the basement membrane of primary and recurrent pterygium, suggesting that the pathogenesis of pterygium may be related to type I and type III allergies [19]. However, according to the clinical manifestations of pterygium development, including tissue degeneration, hypertrophy, hyperplasia, and congestion, it is generally believed that the interaction of immunocytes and inflammatory factors leads to fibroblast proliferation and neovascularization and induces the progression and recurrence of pterygium [1, 20]. Thus, elucidating the upstream mechanisms that regulate fibroblast proliferation and neovascularization, and on this basis, to find a way to prevent pterygium recurrence has become an emergent issue.…”
Section: Discussionmentioning
confidence: 99%
“…A pterygium is a fibrovascular and wing-shaped neoplasm that can invade the cornea and cover the pupil area [1]. Pterygia are common causes of induced astigmatism, ocular movement restriction, and visual impairment [2].…”
Section: Introductionmentioning
confidence: 99%
“…18,19 In Perobatang Village, the proportion of pterygium was 10.7% while the Indonesian Health Survey in 2013 showed the prevalence of pterygium was 8.3% with the highest was in Bali (25.2%) and the lowest was in Banten (3.9%). 4 The prevalence of pterygium was higher in lower latitudes, which has higher sunlight exposure.…”
Section: Discussionmentioning
confidence: 99%